Studi tentang Ketersediaan Obat di Puskesmas Meo-Meo Kota Baubau - Eky Endriana Amiruddin; Waode Iftitah Septarani A (Sarana Ilmu Indonesia (salnesia), 2019)
Planning and procurement of medicine phases is part of that was important in meet the needs of medication at health. For puskesmas Meo-Meo, a problem which often happened that is they did not in accordance between the number of for medicines that are needed and received. The purpose of this study was to find information about the supply of shrubs mainly regarding the process needs planning and procurement of medicine. This type of research was qualitative research using a descriptive approach. The informant in this research consisting of 4 informants that was a responsible for the procurement of medicine in the city health department Baubau, the head of, being responsible for the drug puskesmas, and staff a pharmacy in puskesmas Meo-Meo. Research showed that the availability of drugs in puskesmas Meo-Meo had not been in accordance with the needs. This was closely linked with the data conformity planning procurement medicine, the election medicine and stage compilation the use of medicine. Indicators consumption was the way traveled by researchers to able been given needs a drug used, because consumption drug seen as the projected amount of the drug needs years later. It is suggested that procedures and work systems planning the drug can be adapted to consumption and drug needs to responsible for drug and puskesmas staff Meo-meo to more attention to coordination and the mechanism use of medicine.